2019
DOI: 10.3390/toxins11090535
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Equine Staphylococcus aureus Isolates Exhibiting Reduced Oxacillin Susceptibility

Abstract: The detection of borderline oxacillin-resistant Staphylococcus aureus (BORSA) represents a challenge to both, veterinary and human laboratories. Between 2015 and 2017, 19 equine S. aureus with elevated minimal inhibitory concentrations for oxacillin were detected in routine diagnostics. The aim of this study was to characterize these isolates to identify factors possibly associated with the BORSA phenotype. All S. aureus were subjected to antimicrobial susceptibility testing and whole genome sequencing (WGS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 83 publications
3
24
0
Order By: Relevance
“…However, further in depth analysis of S. cohnii blaZ genes using NCBI BLAST revealed that the sequences only show low identities (< 80%) to any other published staphylococcal blaZ gene. Along with the mecA and mecC gene, the femA and gdpP genes were associated with beta-lactam antibiotic resistance 23 and both genes were detected in the isolates of our study. In general, however, data availability regarding AMR and its respective genes in S. cohnii and S. urealyticus is extremely limited and for this reason it is unclear how reliable the annotation and function of the so far published S. cohnii blaZ genes is.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…However, further in depth analysis of S. cohnii blaZ genes using NCBI BLAST revealed that the sequences only show low identities (< 80%) to any other published staphylococcal blaZ gene. Along with the mecA and mecC gene, the femA and gdpP genes were associated with beta-lactam antibiotic resistance 23 and both genes were detected in the isolates of our study. In general, however, data availability regarding AMR and its respective genes in S. cohnii and S. urealyticus is extremely limited and for this reason it is unclear how reliable the annotation and function of the so far published S. cohnii blaZ genes is.…”
Section: Discussionmentioning
confidence: 52%
“…A borderline oxacillin-resistance in S. aureus isolates due to modified PBPs was previously suggested in a review about methicillin resistance in staphylococci 45 . Moreover, studies recently reported borderline cefoxitin- and oxacillin-resistant S. aureus isolates with substituted PBP amino acid sequences 23 , 46 , 47 . However, in both cases, the borderline resistance was associated with the hyperproduction of the BlaZ beta-lactamase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholtzek et al [ 35 ] characterized equine S. aureus isolates that show elevated minimal inhibitory concentrations (MICs) for oxacillin but could not be categorized as MRSA. Those so-called borderline oxacillin-resistant S. aureus (BORSA) strains pose a challenge for routine laboratories in both human and veterinary medicine if no special procedures and molecular confirmation are practiced.…”
mentioning
confidence: 99%
“…Instead, they are characterized by hyper-production of beta-lactamases or their resistance is associated with point mutations of the PBPs occurring usually in S. aureus . By core genome multilocus sequence typing, Scholtzek et al observed the close relatedness of the isolates belonging to either ST1 or ST1660 [ 35 ]. The beta-lactamase activity of the 19 isolates included was found to be associated with an inducible blaZ gene.…”
mentioning
confidence: 99%